Odpowiedzi

2010-02-27T19:04:54+01:00
A) x²=2 ¼
x²=⁹/₄ | √
x1=³/₂ i x2=-³/₂
x1= 1 ½ i x2=- 1 ½

b) 3x² + 8=x²+58
3x²-x²=58-8
2x²=50 | /2
x²=25 |√
x1=5 i x2=-5

c) 5x² =6,05 | /5
x²=1,21 |√
x1=1,1 i x2=-1,1

d) 5(3-2x²) = 15(x²-1)
15-10x²=15x²-15
-10x²-15x²=-15-15
-25x²=-30 | /(-25)
x²=1,2 | √
x=√1,2
x1=√1,2 x2=-√1,2

e) 2x(x+3)=6(x+x²)-1
2x²+6x=6x+6x²-1
2x²-6x²+6x-6x=-1
-4x²=-1 | /(-4)
x²= ¼ |√
x1=½ i x2=-½

f) 3(x²-3)-x(x+3)=x(x-3)
3x²-9-x²-3x=x²-3x
3x²-x²-x²-3x+3x=9
x²=9 | √
x1=3 i x2=-3

g) x²+⁴/₂ -4=6
x²+2-4=6
x²-2=6
x²=8 |√
x=√8
x1=2√2 i x2=-2√2